Pediatric Hypertension in Two University Hospitals in Cotonou, Benin: Presentation, Etiology, Management and Outcome - d'ALMEIDA HOUNNOU, MARCELLINE SOLANGE EDITH (My University, 2018)
Abstract Background: Hypertension (HPT) is a major public health problem. Many studies have attempted to investigate HPT in school children. Few, however, have targeted hospital HPT. We conducted this study to describe the epidemiologic characteristics, etiologies, management, and outcome of hospital HPT in our setting. Methods: This was a prospective and descriptive study carried out from March 01 through June 30, 2017 in the pediatric departments of two university hospitals: Centre National Hospitalier Universitaire Hubert K. Maga and Centre Hospitalier Universitaire de la Mère et de L’Enfant Lagune of Cotonou, Benin. Every consecutive patient aged 3 to 18 years who was admitted to the two hospitals for any reason had his (her) BP measured. Every patient with HPT was reviewed for demographics, history and clinical examination, and laboratory investigations as appropriate. Management was done accordingly. Outcome was also recorded. Results: The hospital frequency of HPT was 1.98% (31 cases/1565 admissions). The male/female ratio was 1.06 (16 males, 15 females). Mean age was 8.5 years ± 4.39 (range, 3 to 16 years). 74.19% patients had Body mass index within −2SD and +2SD. Only one patient had BMI above +3SD. The main etiologies found were renal: acute tubular necrosis (45.16%), acute glomerulonephritis (16.13%), and acute pyelonephritis (12.90%). Diuretics (64.5%), were the main antihypertensive drugs used. A single drug therapy was used in 35.4%, a two-drug therapy in 32.2% and a three-drug therapy in 9.6% of cases. Length of hospital stay was more than one week in 70.97% of cases. Hospital death rate for HPT was 19.35%. The outcome was not known in one patient due to exit from hospital against medical advice. All the other patients fully recovered at one month post-discharge follow-up. Conclusion: HPT presents as a symptomatic disease in our hospitals; it has a renal etiology in most cases and has significant death rate despite treatment. Advocacy with health authorities must be the way out of issues of HPT management in our setting.
Keywords: Hypertension; Hospital; Children; Benin